An audit of the results of ultrasound‐guided core needle biopsy of mammography versus ultrasound screen‐detected breast lesions. Issue 5 (9th February 2017) - Rhee, Sun Jung; Han, Boo‐Kyung; Ko, Eun Sook; Choi, Ji Soo; Ko, Eun Young
ABSTRACT: Purpose: To analyze the malignancy rate of ultrasound‐guided core needle biopsy (US‐CNB) for screen‐detected breast lesions and to evaluate the results according to the mode of detection of the target lesions. Methods: This is a retrospective review of 703 consecutive women who underwent US‐CNB for screen‐detected breast lesions at a single tertiary hospital. Breast Imaging Reporting and Data System (BI‐RADS) categories and histopathological results of the target lesions were assessed. The cases were divided into two groups: the mammography‐based detected lesions (M‐group) and the US‐based detected lesions (U‐group). The biopsy performances of the two groups were compared using the χ 2 test. Results: The malignancy rate in the entire population was 22.0%: 0.8%, 12.3%, 65.2%, 89.3%, and 94.6% in BI‐RADS categories 3, 4A, 4B, 4C, and 5, respectively. The malignancy rate was significantly higher in the M‐group (54.1% [79/146]) than in the U‐group (13.6% [76/557]) ( p < 0.001). BI‐RADS category 3 was the most common assessment overall that led to a US‐CNB (362/703, 51.5%) and the rate of BI‐RADS category 3 diagnoses that led to US‐CNB was significantly higher in the U‐group ( p < 0.001). Conclusions: The malignancy rate associated with US‐CNB for screen‐detected breast lesions was 22.0%. The breast lesions detected by mammography have a higher malignancy rate than those detected by US. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :261–266, 2017